Current Development and Application on Inclusion of Herbal Phytochemicals in Novel Herbal Drug Delivery System - Ahmed, Aziz; Ahmad, Rizwan; Jangir, Shurbhi; Sharma, Deeksha (Natural Products Journal, The, 2025)
Herbal phytochemicals as secondary metabolites are present in herbal medicines. Herbal medicines can be used to treat a wide range of illnesses and diseases. The Novel herbal drug delivery system approach includes transfersomes, ethosomes, microspheres, phytosomes, liposomes, polymeric nanoparticles, and nanocapsules. The novel herbal drug delivery systems have several benefits over conventional herbal remedies. Herbal medicines are less expensive and have fewer serious side effects than generic medications. The novel herbal drug delivery systems have several benefits over conventional herbal remedies. These include improved solubility and bioavailability, protection from side effects, improved pharmacological action, increased stability, better delivery to tissue macrophages, consistent delivery, and defense against active ingredients' physical and chemical breakdown. There is a need for a novel method of active components of drugs to apply on target organs or sites of the human body to avoid repeated administration of dosage forms and enhance patient adherence. Scientists have tried to focus on advanced mechanisms or processes for delivering herbal components into the human body. Novel Herbal Drug Delivery System helps to boost drug efficacy by lessening side effects and enhancing the blood level of the drug. Novel herbal formulations can reduce recurrent administration of medicines and noncompliance of patients.
Keywords: liposome